Flipping confidential : - Kemp, Kirsten (John Wiley & Sons, 2007)
This book establishes a new standard for real estate authors. Kirsten Kemp gives her readers delightfully written prose packed with her wealth of experiences. The author lays out so many profit-generating (and loss-avoiding) ideas that while reading the manuscript my highlighter never got a rest.Real estate isn't just for the rich! And this book proves it. In Flipping Confidential, Kirsten Kemp gives first-time investors the guidance and inside tips to buy cheap, fix fast, and sell high. With a positive attitude and a healthy dose of humor, Kirsten Kemp walks you through every step of a successful flip—from finding the right house to getting your financing in order, from making big improvements to pricing the home to sell